2021
DOI: 10.2147/ijgm.s295939
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-155 and JAK2/STAT3 Axis in Acute Ischemic Stroke Patients and Its Relation to Post-Ischemic Inflammation and Associated Ischemic Stroke Risk Factors

Abstract: Background “Micro RNAs and their target genes recently have been identified to play a crucial role in the molecular pathogenesis of post-stroke ischemic cellular injury, which elucidates their new role in ischemic stroke diagnosis and therapy”. Thus, we evaluated the relative serum expression of miR-155, an inflammatory micro RNA, and the mRNAs (JAK2/STAT3) in acute ischemic stroke patients and its associations with the inflammatory cytokine TNF-α and different stroke risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 77 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The increase in miR-155 expression was associated with a significant increase in JAK2/STAT3 expression in correlation with increased levels of TNF-α. It has been shown that these high levels of expression could trigger post-stroke cell inflammation and miR-155 could be used as a potential inflammatory biomarker for the acute phase of IS [ 93 ].…”
Section: Mir-155mentioning
confidence: 99%
“…The increase in miR-155 expression was associated with a significant increase in JAK2/STAT3 expression in correlation with increased levels of TNF-α. It has been shown that these high levels of expression could trigger post-stroke cell inflammation and miR-155 could be used as a potential inflammatory biomarker for the acute phase of IS [ 93 ].…”
Section: Mir-155mentioning
confidence: 99%
“…The involvement of the JAK2/STAT3 pathway is crucial in the pathological process underlying ischemic stroke 43 , 44 . The increased expression of JAK2/STAT3 observed in individuals suffering from acute ischemic stroke may contribute to cellular inflammation 45 . IL-17 plays an important role in contributing to secondary damage and inflammation in post-ischemic stroke 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have observed that STAT3 expression levels were increased in the rat brain regions ipsilateral to middle cerebral artery occlusion (MCAO) relative to the sham group (15, 16). Moreover, Adly et al also found elevated levels of STAT3 in the peripheral blood of patients with IS compared to controls, indicating that STAT3 may act as a vital player in the pathogenesis of IS (17). Mechanically, Agrawal et al found that in an oxygen-glucose deprivation and reperfusion (OGD-R) model of PC12 cells, considerable reactive oxygen species (ROS) were generated, which could trigger the expression of STAT3 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Adly et al. also found elevated levels of STAT3 in the peripheral blood of patients with IS compared to controls, indicating that STAT3 may act as a vital player in the pathogenesis of IS ( 17 ). Mechanically, Agrawal et al.…”
Section: Discussionmentioning
confidence: 99%